Analysis on Climate Literacy Capacity of Level XI High School Students in Surabaya - Hasna’ Nabilah; Eko Hariyono (IKIP Mataram, 2021)
The climate problem today caused damage to infrastructures and many other living elements among mankind. As the prospected future leaders, students need to understand and to respond the effects of climate change. A person with climate literacy may enhance their ability and capacity to face climate challenges in the future. Climate literacy is the understanding of the influence of self and society on the climate. This research is conducted to give a general picture of climate literacy among high school students in Surabaya and each indicator in climate competency aspects. The methodology used in this research is a descriptive qualitative method. The research instrument used in this research is a climate literacy test. The valuation of climate literacy capacity of the students being done by giving scores manually from the test answers according to the scoring guideline in the scoring rubric and achievement results with categories as very high, high, moderate, low, and very low. The research samples are 107 high school students at level XI in SMAN 22 Surabaya (Public High School 22 Surabaya). According to the research, the students’ indicator in scientific identifying is low with a score percentage of 48.9%. The students’ indicator in explaining the scientific phenomenon is moderate with a score of 74.5%, while students’ indicator score in using scientific evidence is moderate with 68.6%. It could be said that high school students in SMAN 22 Surabaya as a whole have a moderate climate literacy capacity with a percentage score of 64%.